Mahabbah, Rahmah, dan Ihsan dalam Kurikulum Berbasis Cinta: Integrasi Nilai Cinta pada Pendidikan Islam di Indonesia - Raharjo, Harmanto; Irpan Hilmi; Aulia Rahmi; Supiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the integration of love values into Islamic education policy in Indonesia, positioning the Love-Based Curriculum (Kurikulum Berbasis Cinta, KBC) as a form of their actualization. It focuses on four matters that have tended to be examined separately: the philosophical foundation of love values, the form of their integration into policy, their alignment with the goals and direction of Islamic education policy, and the opportunities and challenges of their implementation. The research uses a descriptive-analytical library research method, with KBC policy documents as primary data and relevant academic literature as secondary data, analyzed through content analysis and policy analysis. The findings reveal three main points. First, the love values formulated in mahabbah, rahmah, and ihsan possess a conceptual continuity with the five core values (Panca Cinta) of the KBC, so that they can be translated from a normative idea into a curricular framework. Second, love values are integrated into Islamic education policy through the dimensions of purpose, process, and culture, while the KBC broadens their scope to ecological responsibility and love of the homeland. Third, the principles of the KBC align with Islamic education policy in purpose, values, and approach, although their implementation faces challenges in academic orientation, educator readiness, and the evaluation system. The novelty of this study lies in reading the KBC as a meeting point between love values in the Islamic tradition and contemporary education policy, with implications for strengthening the humanistic orientation of Islamic education policy in Indonesia.